Prevailing Government Maternal Health Care System and Challenges Faced by Health Professionals: A Case study in Tehsil Jampur - Ghani, Altaf; Hashmi, Hassam Ahmad; Sadaf, Dure (Pakistan Journal of Humanities and Social Sciences, 2023)
This research aims to investigate maternal healthcare facilities and the challenges faced by the health professionals in tehsil Jampur. The present study utilized a qualitative approach and collected data from 23 participants through purposive sampling. The population of Tehsil Jampur in the Punjab province of Pakistan predominantly resides in rural areas. The data was collected via in-depth interviews and analyzed using a straightforward thematic analysis methodology. Services provided at primary healthcare units endeavor to met service-provision standards by arranging, LHVs, LHWs, LHS, CMWs, transportation, nutrition etc. but it requires to highlighting the importance of addressing staff absenteeism, inadequate infrastructure, and inconsistent working hours to improve health outcomes. It also reveals that due to multiple deficiencies, the assessment of service quality at facility centers is of utmost importance. The challenges encompass insufficient medicine accessibility, restricted service hours, inconvenient transportation to remote medical facilities, male exclusion as partaker of health program, traditional practices including reliance on TBAs and a scarcity of female healthcare providers influenced by cultural norms pertaining to gender dynamics. The health sector’s governance is adversely affected by the frequent fluctuations in government and its system. The health department experiences instability due to the varying strategies, programs, and staff appointments introduced by successive prime ministers.